PERFORMAN BROILER YANG DIBERI SUPLEMEN â€œPUYER HERBALâ€ - Deta, Yonatan; Setiyawan, Ahmad Iskandar; Supartini, Nonok (Universitas Tribhuwana Tunggadewi, 2017)
Broilers who are given synthetic antibiotics will produce less healthy meat to consumption, due to the residue of chemicals contained in the meat. kunyit, kencur and temulawak are plants that contain curcumin and atsiri oils. This active substance can replace antibiotics to improve performance and quality of meat broiler. The aim of this study to determine the effect of puyer herbal as supplement on broiler performance which includes the consumption of rations, weight gain and fed conversion. This research was conducted on 28 March 2017 - 01 May 2017 At the Agricultural Laboratory of Tribhuwana Tunggadewi University Malang. The material used is DOC amounted to 80 chick with the average body weight of 50.39 grams / chick, kunyit, kencur and temulawak. The method used was experimental method using completely randomized design, with 4 treatments and 4 replications. Each treatment with detail P0 = giving of ration without puyer herbal, P1 = giving of ration + puyer herbal 0,3%, P2 = giving of ration + puyer herbal 0,6%, P3 = giving of ration + puyer herbal 0,9%. the data were analyzed by RAL, if any real different will be tested by BNT test. The results of the study showed that using puyer herbal in the ration gave a very real signifancantly diferent on ration consumption, body weight gain and fed conversion. The highest ration consumption was in P3 that is 3267,25 gram / chick, the highest body weight gain in P3 is 39,67 gram / chick and the lowest fed conversion at P3 that is 2,27 / chick. the results of the study can be concluded that the provision of puyer herbal as supplements gave a very real effect on the research variables at the level of supplementation 0.9%. It is recommended if there is application about giving herbal powder supplements on broiler, as well as given with level 0,9%. Broiler yang diberi antibiotik sintetik akan menghasilkan daging yang kurang sehat untuk dikonsumsi, disebabkan residu bahan ? bahan kimia yang terdapat dalam dagingnya. Kunyit, kencur dan temulawak merupakan tanaman yang memiliki kandungan kurkumin dan minyak atsiri. Zat aktif ini mampu menggantikan fungsi antibiotik sintetik didalam tubuh ayam broiler. Seperti memperbaiki performan dan kualitas daging. Tujuan penelitian ini untuk mengetahui pengaruh suplemen puyer herbal terhadap performan broiler yang meliputi konsumsi ransum, pertambahan bobot badan dan konversi ransum. Penelitian ini dilaksanakan pada tanggal 28 maret 2017 - 01 mei 2017 Di Laboratorium Pertanian Universitas Tribhuwana Tunggadewi Malang. Materi yang digunakan yaitu DOC berjumlah 80 ekor dengan rataan bobot badan 50,39 gram/ekor, kunyit temulawak dan kencur. Metode yang digunakan adalah rancangan acak lengkap, dengan 4 perlakuan dan 4 ulangan. Setiap perlakuan dengan rincian P0 = pemberian ransum tanpa puyer herbal, P1 = pemberian ransum + puyer herbal 0,3 %, P2 = pemberian ransum + puyer herbal 0,6 %, P3 = pemberian ransum + puyer herbal 0,9 %. Data penelitian dianalisis menggunakan RAL, jika terdapat perbedaan yang sangat nyata akan diuji lanjut dengan uji BNT. Dari hasil penelitian menunjukkan pemberian suplemen puyer herbal memberikan pengaruh yang sangat nyata terhadap konsumsi ransum, pertambahan bobot badan dan konversi ransum. Konsumsi ransum tertinggi terdapat pada P3 yaitu 3267,25 gram/ekor, pertambahan bobot badan tertinggi pada P3 yaitu 39,67 gram/ekor dan konversi ransum terendah pada P3 yaitu 2,27/ekor. Dengan demikian hasil penelitian dapat disimpulkan bahwa pemberian suplemen puyer herbal memberikan pengaruh yang sangat nyata terhadap variabel penelitian pada level pemberian suplemen 0,9 %. Disarankan apabila ada penerapan mengenai pemberian suplemen puyer herbal pada broiler, sebaik diberikan dengan level 0,9 %.